2017
DOI: 10.1182/bloodadvances.2017007229
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1–targeted thrombomodulin mitigates tissue factor–driven inflammatory thrombosis in a human endothelialized microfluidic model

Abstract: Key Points• A microfluidic model of TF-driven thrombosis allows testing of human-specific, antibody-targeted therapeutics in whole blood under flow.• hTM/R6.5 inhibits inflammatory thrombosis more effectively than untargeted agents (eg, shTM) and shows synergy with supplemental PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 65 publications
2
51
0
Order By: Relevance
“…Microchannels were endothelialized with human umbilical vein endothelial cells as described previously, 37 which typically resulted in complete coverage of the microchannels. Channels were treated with tumor necrosis factor-a (TNF-a; 10 ng/mL) under flow (at shear stress of 5 dyne/cm 2 ) for 6 hours to flow condition and induce activation prior to exposure to whole blood.…”
Section: Microfluidic Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Microchannels were endothelialized with human umbilical vein endothelial cells as described previously, 37 which typically resulted in complete coverage of the microchannels. Channels were treated with tumor necrosis factor-a (TNF-a; 10 ng/mL) under flow (at shear stress of 5 dyne/cm 2 ) for 6 hours to flow condition and induce activation prior to exposure to whole blood.…”
Section: Microfluidic Assaymentioning
confidence: 99%
“…37 In this model, fully endothelialized microchannels are activated with an inflammatory mediator (eg, TNF-a), inducing leukocyte and platelet adhesion and widespread fibrin generation when the channels are exposed to flowing human whole blood. We hypothesized that if the fusions maintain their activity in whole blood, they would significantly reduce fibrin and platelet deposition in response to inflamed endothelium.…”
Section: Therapeutic Effectiveness Of Rbc Cargoesmentioning
confidence: 99%
See 1 more Smart Citation
“…An explanation for this is that at high TF levels, the amounts of thrombin formed under flow are too high to be targeted the coagulation factor‐inactivating thrombomodulin. In an inflammatory endothelial model, it was also found that the introduction of thrombomodulin suppresses fibrin deposition …”
Section: Discussionmentioning
confidence: 96%
“…Our approach herein differs from other vessel‐on‐a‐chip methods, mostly using a confluent monolayer of endothelial cells, which is activated with tumor necrosis factor‐α or is damaged mechanically or by FeCl 3 . Those methods can be considered to reflect conditions of inflammation or severe endothelial injury and may lack the presence of a “healthy” endothelium.…”
Section: Discussionmentioning
confidence: 99%